From capability to concept: Fusion of systems analysis techniques for derivation of future - Sparks, Emma S. (Cranfield University, 2007)
The intent of this thesis is to define a set of processes for use within UK Government dismounted soldier systems research that will provide stakeholders with auditable and traceable information to understand gaps in military capability and justify future procurement decisions. The need for this approach is linked to organisational shifts within the UK Ministry of Defence, and more specifically Government research with the move towards procurement of capability rather than equipment. In conjunction with reducing defence budgets and increased scrutiny, there is a need to prioritise spending to those areas that will provide the most significant enhancement to operational effectiveness. The proposed process suite provides underpinning data to support Government decisions, from definition of military need through to concept design and prioritisation of future research activities. The approach is grounded in the field of systems thinking and systems engineering providing the logical and systematic constructs required for highly complex systems where the human is a central focus. A novel fusion of existing systems tools and techniques enables both subjective data from domain experts and objective data in the form of operational analysis and field trials to be utilised for analysis across the five NATO capability domains, with output defining the relative importance of survivability, sustainability, mobility, lethality and C4I in the context of operational and strategic level military goals as well as wider challenges represented by the doctrinal defence lines of development. Future developments should include alignment with developing pan-MoD initiatives in the form of MODAF, if required by the customer organisation. This would enable generic versions of the process suite to be applied to any defence domain and problem.